THE EFFECT OF DIFFERENT KAINDS OF BAITS TO CATCH TRAPS FISH AGREGATING DEVICE ( FADs ) IN TELUK RHU VILLAGE, IN NORTH RUPAT DISTRICT BENGKALIS REGENCY OF RIAU PROVINCES - Rengi, Pareng; ', Rahmadi; ', Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted on January 25 until February 04 2016, the waters a rown Fish Agregating device ( FADs ) in Teluk Rhu village North Rupat Districth of Bengkalis in Riau province. In order to know effect differen lure on catches and the type of fish that is in the bottom waters . The method used is the method of experiment ,data collection was done by direct observation in the field. The research has been carried out with four kainds of bait are ( u1 ) fish (Chirocentrus dorab), ( u2 ) shrimp, ( U3 ) fish (Iiisha elogante) and ( u4 ) control . The catch of fish based on the individual and the weight of at most 113 tails / 1661 gram and at least 48 tails / 1421 grams ( u4 ). Based on the kaind of fish caught the most gulamah fish ( Pseudocienna amovensis ) as many as 125 tails weighing 1971 grams and the least is a gutter fish ( chorine mustala ) as much as 9 tails with a weight of 1209 grams .Keywords: Fish Agregating Device ( FADs ), Bait, Traps Fishing